Financial Reform: What Shakes It? What Shapes It? - Abiad, Abdul; Mody, Ashoka (American Economic Review, 2005)
What accounts for the worldwide advance of financial reforms in the last quarter century? Using a new index of financial liberalization, we find that influential events shook the policy status quo. Balance-of-payments crises spurred reforms, but banking crises set liberalization back. Falling global interest rates strengthened reformers, while new governments went both ways. The overall trend toward liberalization, however, reflected pressures and incentives generated by initial reforms that raised the likelihood of additional reforms, stimulated further by the need to catch up with regional reform leaders. In contrast, ideology and country structure had limited influence.